Urinary Schistosomiasis around Oyan Reservoir, Nigeria: Twenty Years after the First Outbreak - OP Akinwale; MB Ajayi; DO Akande; PV Gyang; MA Adeleke; AK Adeneye; MO Adebayo; AA Dike (Tehran University of Medical Sciences, 2010)
"nBackground: Oyan reservoir, South-West Nigeria was constructed in 1984 to generate electricity but has altered the existing physical, biological and socio-economic environment of the people. This study, carried out between October 2006 and March 2008, aimed at investigating the current status of Schistosoma haematobium infection around the reservoir."nMethods: Urine samples from 536 participants in five communities were examined for haematuria using reagent strips and S. haematobium ova was detected using sedimentation by gravity method. The participants were drawn from Abule Tuntun (n= 115), Ibaro (n= 156), Imala Odo (n= 88), Imala (n= 103) and Apojula (n= 74) communitie."nResults: Prevalence rates by haematuria were (Abule Tuntun- 33.04%; Ibaro- 73.07%; Imala odo- 60.22%; Imala- 7.77%; Apojula - 39.19%) and by presence of parasite ova were (Abule Tuntun- 39.13%; Ibaro- 83.97%; Imala Odo- 62.5%; Imala- 20.39%; Apojula- 54.05%)."nConclusion: S. haematobium transmission has been sustained in the reservoir since the outbreak was first reported in 1988. Mass treatment with praziquantel was conducted 8 years ago (2001) in two of the communities. However, the infection has persisted due to lack of pipe borne water and safe waste disposal system.